Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4274/tjo.galenos.2018.80588
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on Macular, Choroidal, and Retina Nerve Fiber Layer Thickness

Abstract: Objectives:This study aimed to compare the thickness of the macula, choroid, and peripapillary retina nerve fiber layer (RNFL) in smokers with those of healthy, nonsmoking individuals using spectral domain optical coherence tomography (SD-OCT).Materials and Methods:Sixty-eight healthy smokers with an average of 19.75 pack-years and 71 nonsmoker subjects (control group) were included in the study. Macular thickness, RNFL thickness, and choroidal thickness (CT) were measured by SD-OCT.Results:The mean age of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Using OCTA we found no significant difference between both groups as regards the CMT (foveal subfield thickness) and the temporal parafoveal subfield thickness, but other macular subfields thickness was significantly lower in the smokers group. Other studies using either OCTA 5,12 or OCT 1419 found that there was no significant difference in CMT between smokers and non-smokers. All of these results were matching with our study findings.…”
Section: Discussionmentioning
confidence: 91%
“…Using OCTA we found no significant difference between both groups as regards the CMT (foveal subfield thickness) and the temporal parafoveal subfield thickness, but other macular subfields thickness was significantly lower in the smokers group. Other studies using either OCTA 5,12 or OCT 1419 found that there was no significant difference in CMT between smokers and non-smokers. All of these results were matching with our study findings.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, these data are in accordance with the results from a recent meta-analysis [ 6 ] where a positive correlation between current or former smoking and global cpRNFLT was also found in the Rotterdam II and in the Montrachet Study [ 6 ]. A further small case-control study by Teberik [ 39 ] also shows numerically thicker RNFL in the three nasal sectors (but the statistical significance has been achieved only in the NI sector). As smoking potentially interferes with lipid profile [ 40 ], we investigated the mediating effects of smoking status and lipid profile.…”
Section: Discussionmentioning
confidence: 98%
“…Here, the two inner retinal layers, the retinal nerve fibre layer (RNFL) and ganglion cell inner plexiform layer (GCIPL), taper to non-existence at the centre, the fovea, allowing less light scattering for incoming photons and so providing the region of highest acuity vision (Figure 1B) [1]. The morphology of the macula has been studied previously, with variation in physiology associated with ethnicity [2, 3], age [4, 5] and lifestyle variables such as smoking [6]. There are also several diseases that exhibit changes in the thickness of the inner retina, such as multiple sclerosis [7, 8], diabetic retinopathy [9, 10], Parkinson’s disease [11] and other neurological disorders [12, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%